Development and validation of a rapid and easy-to-perform point-of-care lateral flow immunoassay (LFIA) for the detection of SARS-CoV-2 spike protein - Mohammad, Shamim; Wang, Yuxia; Cordero, John; Watson, Christopher; Molestina, Robert; Rashid, Sujatha; Bradford, Rebecca (Frontiers in Immunology, 2023)
Development and validation of rapid and easy-to-perform diagnostics continue to be a high priority during the current COVID-19 pandemic. Although vaccines are now widely available, early detection and consistent transmission control provide ideal means to mitigate the spread of SARS-CoV-2. Nucleic acid-based real‐time PCR tests are widely acknowledged as the gold standard for reliable diagnosis of COVID-19 infection. These tests are based on detecting viable or nonviable viral nucleic acids. SARS-CoV-2 spike protein is an alternative and ideal target for SARS-CoV-2 diagnosis in the early phase of infection, but point-of-care kits to detect the SARS-CoV-2 spike protein are limited. Here we describe a rapid and convenient method based on Lateral Flow Immunoassay (LFIA) to detect SARS-CoV-2 spike proteins, including SARS-CoV-2 variants (A.23.1, B.1.1.1, 1.617.2, B.1.1.7, B.1.351, P.1, N501Y, R, UK, and South African) within 5 to 10 minutes. We generated highly specific monoclonal antibodies (mAbs) against rationally designed SARS-CoV-2 spike protein. Matched pair mAbs were selected by epitope mapping and employed as antigen capture reagents by spotting onto a nitrocellulose membrane and as detector reagents by conjugation with colloidal gold nanoparticles. We evaluated the performance of the LFIA using recombinant spike proteins of SARS-CoV-2 and several SARS-CoV-2 variants. The specificity of the LFIA was assessed using heat-inactivated SARS-CoV-2 and related human coronaviruses (HCoV-OC43, HCoV-229E, HCoV-HKU1, and HCoV-NL63) and an FDA-approved respiratory pathogens (RP) panel. The assay exhibited 98% specificity and acceptable performance with respect to the minimum limit of detection (25 ng/test) in validation tests. This new LFIA provides improved performance for the early diagnosis of SARS-CoV-2, particularly for home monitoring and in situations with limited access to molecular methods.